2013
DOI: 10.1103/physrevlett.110.087207
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Ferromagnetism in Chemically Ordered FeRh Nanocrystals

Abstract: In sharp contrast to previous studies on FeRh bulk, thin films, and nanoparticles, we report the persistence of ferromagnetic order down to 3 K for size-selected 3.3 nm diameter nanocrystals embedded into an amorphous carbon matrix. The annealed nanoparticles have a B2 structure with alternating atomic Fe and Rh layers. X-ray magnetic dichroism and superconducting quantum interference device measurements demonstrate ferromagnetic alignment of the Fe and Rh magnetic moments of 3 and 1 B , respectively. The ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 39 publications
1
39
0
1
Order By: Relevance
“…73 In contrast with thin films, stripes and larger nanoparticles, Hillion and coworkers found that small (,5 nm) nanoparticles retained the high-temperature FM state until low temperatures (down to 3 K) suggesting a rich size-dependent phase diagram for the FeRh system. 74 As numerous examples illustrate, the FeRh system is probably the magnetocaloric system that has profited the most from the size-reduction route, unveiling promising technological advantages (such as the reduction of the magnetic irreversibility) and interesting new physical states. In the near future, more detailed nanoparticles size-dependent studies should help understand what are the main mechanisms driving the magnetic ordering at this scale.…”
Section: Ferhmentioning
confidence: 99%
“…73 In contrast with thin films, stripes and larger nanoparticles, Hillion and coworkers found that small (,5 nm) nanoparticles retained the high-temperature FM state until low temperatures (down to 3 K) suggesting a rich size-dependent phase diagram for the FeRh system. 74 As numerous examples illustrate, the FeRh system is probably the magnetocaloric system that has profited the most from the size-reduction route, unveiling promising technological advantages (such as the reduction of the magnetic irreversibility) and interesting new physical states. In the near future, more detailed nanoparticles size-dependent studies should help understand what are the main mechanisms driving the magnetic ordering at this scale.…”
Section: Ferhmentioning
confidence: 99%
“…A limited system size restricts the maximum extent of nucleated domains of each ordering and hence the size of the interface region. Experimental observations of small FeRh nanoparticles [20] and thin films [21] have also shown a large increase in the thermal hysteresis and even the suppression of the AFM phase [22]. 3.48 .…”
mentioning
confidence: 99%
“…While it has long been known that the bcc FeRh unit cell volume expands upon transforming to the FM order [30], we use EXAFS experiments to determine the local iron environment before and after annealing. From a quantitative FEFFIT analysis at the Fe K edge on FeRh nanoparticle, we confirmed the systematic transition upon annealing from the chemically disordered fcc (A1) phase to the ordered CsCl-type (B2) structure for 3 nm FeRh clusters assemblies embedded in a carbon matrix [13]. In the latter case, the unit cell size has been found compatible with those of B2 FeRh bulk material with a Debye–Waller (DW) factor decreasing with chemical ordering.…”
Section: Discussionmentioning
confidence: 54%
“…1), we obtained the experimental persistence of high ferromagnetic magnetization down to 3 K for size-selected chemically ordered B2-like FeRh nanocrystals up to 5 nm in diameter. In particular, magnetic measurements on annealed 3.3 nm FeRh samples, have demonstrated ferromagnetic alignment of Fe and Rh at low temperatures with respective values of 3μ B and 1μ B [13]. The ferromagnetic order increases slightly for smaller nanoparticles as confirmed from XMCD measurements on annealed 2 nm FeRh (see Fig.…”
Section: Discussionmentioning
confidence: 78%